Large Enhancement of 2D Electron Gases Mobility Induced by Interfacial Localized Electron Screening Effect. Issue 22 (17th April 2018) - Chi, Xiao; Huang, Zhen; Asmara, Teguh C.; Han, Kun; Yin, Xinmao; Yu, Xiaojiang; Diao, Caozheng; Yang, Ming; Schmidt, Daniel; Yang, Ping; Trevisanutto, Paolo E.; Whitcher, T. J.; et al.
Abstract: The interactions between delocalized and localized charges play important roles in correlated electron systems. Here, using a combination of transport measurements, spectroscopic ellipsometry (SE), and X‐ray absorption spectroscopy (XAS) supported by theoretical calculations, we reveal the important role of interfacial localized charges and their screening effects in determining the mobility of (La0.3 Sr0.7 )(Al0.65 Ta0.35 )O3 /SrTiO3 (LSAT/SrTiO3 ) interfaces. When the LSAT layer thickness reaches the critical value of 5 uc, the insulating interface abruptly becomes conducting, accompanied by the appearance of a new midgap state. This midgap state emerges at ≈1 eV below the Ti t 2g band and shows a strong character of Ti 3d xy – O 2p hybridization. Increasing the LSAT layer from 5 to 18 uc, the number of localized charges increases, resulting in an enhanced screening effect and higher mobile electron mobility. This observation contradicts the traditional semiconductor interface where the localized charges always suppress the carrier mobility. These results demonstrate a new strategy to probe localized charges and mobile electrons in correlated electronic systems and highlight the important role of screening effects from localized charges in improving the mobile electron mobility at complex oxide interfaces. Abstract : The interactions between delocalized and localized charges play important roles in correlated electron systems. From a newly designed LSAT/STO 2DGEs system, a new interfacial midgap state is found, and localized electrons in this new state have significantly influence on electron mobility. The increasingly localized electrons amplify the electron mobility, providing a new way to improve the interfacial electronic mobility.